Caffeamide 36-13 Regulates the Antidiabetic and Hypolipidemic Signs of High-Fat-Fed Mice on Glucose Transporter 4, AMPK Phosphorylation, and Regulated Hepatic Glucose Production. (20th July 2014) - Kuo, Yueh-Hsiung; Lin, Cheng-Hsiu; Shih, Chun-Ching
Abstract : This study was to investigate the antidiabetic and antihyperlipidemic effects of (E)-3-[3, 4-dihydroxyphenyl-1-(piperidin-1-yl)prop-2-en-1-one] (36-13 ) (TS), one of caffeic acid amide derivatives, on high-fat (HF-) fed mice. The C57BL/6J mice were randomly divided into the control (CON) group and the experimental group, which was firstly fed a HF diet for 8 weeks. Then, the HF group was subdivided into four groups and was given TS orally (including two doses) or rosiglitazone (Rosi) or vehicle for 4 weeks. Blood, skeletal muscle, and tissues were examined by measuring glycaemia and dyslipidemia-associated events. TS effectively prevented HF diet-induced increases in the levels of blood glucose, triglyceride, insulin, leptin, and free fatty acid (FFA) and weights of visceral fa; moreover, adipocytes in the visceral depots showed a reduction in size. TS treatment significantly increased the protein contents of glucose transporter 4 (GLUT4) in skeletal muscle; TS also significantly enhanced Akt phosphorylation in liver, whereas it reduced the expressions of phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase). Moreover, TS enhanced phosphorylation of AMP-activated protein kinase (phospho-AMPK) both in skeletal muscle and liver tissue. Therefore, it is possible that the activation of AMPK by TS resulted in enhanced glucose uptake in skeletal muscle, contrasting with diminished gluconeogenesis in liver. TS exhibits hypolipidemic effect by decreasing the expressions of fatty acid synthase (FAS). Thus, antidiabetic properties of TS occurred as a result of decreased hepatic glucose production by PEPCK and G6Pase downregulation and improved insulin sensitization. Thus, amelioration of diabetic and dyslipidemic state by TS in HF-fed mice occurred by regulation of GLUT4, G6Pase, and FAS and phosphorylation of AMPK.